2015
DOI: 10.1242/jcs.169342
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylsphingosine (psychosine)-induced demyelination is attenuated by sphingosine 1-phosphate signalling

Abstract: Globoid cell leukodystrophy (Krabbe disease) is a rare infantile neurodegenerative disorder. Krabbe disease is caused by deficiency in the lysosomal enzyme galactocerebrosidase (GALC) resulting in accumulation, in the micromolar range, of the toxic metabolite galactosylsphingosine ( psychosine) in the brain. Here we find that psychosine induces human astrocyte cell death probably via an apoptotic process in a concentration-and time-dependent manner (EC50∼15 μM at 4 h). We show these effects of psychosine are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 51 publications
10
64
1
Order By: Relevance
“…Exposure to Yoda‐1 or psychosine caused similar levels of demyelination (Figure g). We have previously reported that psychosine induces demyelination of organotypic cerebellar slices (Misslin et al, ; O'Sullivan & Dev, ) and have used this system as an ex vivo model of the dysmyelination that occurs in Krabbe disease (Giri et al, ). Importantly, blocking Piezo1 channels with GsMTx4 prevented psychosine‐mediated demyelination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to Yoda‐1 or psychosine caused similar levels of demyelination (Figure g). We have previously reported that psychosine induces demyelination of organotypic cerebellar slices (Misslin et al, ; O'Sullivan & Dev, ) and have used this system as an ex vivo model of the dysmyelination that occurs in Krabbe disease (Giri et al, ). Importantly, blocking Piezo1 channels with GsMTx4 prevented psychosine‐mediated demyelination.…”
Section: Resultsmentioning
confidence: 99%
“…Galactosylsphingosine or psychosine (Santa Cruz Biotechnology, sc-202781) is a cationic lysosphingolipid that accumulates in the brains of patients with Krabbe disease (Giri et al, 2002) and causes oligodendrocyte cell death and demyelination (Misslin, Velasco-Estevez, Albert, O'Sullivan, & Dev, 2017;O'Sullivan & Dev, 2015).…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…9063 and 11065), as per the ethics outlined by the supplier and as we have described previously [41, 4648]. Human astrocytes were cultured at 37 °C and 5 % CO 2 in a humidified incubator and grown in human astrocyte speciality media (ScienCell; 1801) or standard DMEM/F12 media (Fisher; 10770245) supplemented with 1 % astrocyte growth supplement (ScienCell; 1852), 10 % fetal bovine serum (FBS, Sigma; F7524) and 1 % penicillin/streptomycin (pen/strep, Sigma; P4333) in T75 culture flasks (Corning) unless otherwise indicated in the figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…It is currently marketed as Gilenya for use in multiple sclerosis patients to reduce the relapse rate and lessen disease progression. In vitro studies show that fingolimod, when added 1 hr before psychosine, was able to attenuate psychosine‐induced death of astrocytes and lessen decreases of mitochondria membrane potential in astrocytes (O'Sullivan and Dev, ). Fingolimod also reduced psychosine‐elicited demyelination in a cerebellar slice preparation (O'Sullivan and Dev, ).…”
Section: Biosynthesis Pathway Of Galactosylceramidementioning
confidence: 99%